Mr. Emerson's Revolution - Jean McClure Mudge
This volume traces the life, thought and work of Ralph Waldo Emerson, a giant of American intellectual history whose transformative ideas greatly strengthened the two leading reform issues of his day: abolition and women's rights. A broad and deep, yet cautious revolutionary, he spoke about a spectrum of inner and outer realities-personal, philosophical, theological and cultural-all of which gave his mid-career turn to political and social issues their immediate and lasting power. This multi-authored study frankly explores Emerson's private prejudices against blacks and women alongside his public championing of their causes. Such a juxtaposition freshly charts the evolution of Emerson's slow but steady application of his early neo-idealism to emancipating blacks and freeing women from social bondage. His shift from philosopher to active reformer had lasting effects not only in America but also abroad. In the U.S. Emerson influenced such diverse figures as Thoreau, Whitman, Dickinson and William James; in Europe he shaped Mickiewicz, Wilde, Kipling, Nietzsche, and Camus; moreover, he had many leading followers in India and Japan. The book includes over 160 illustrations, among them eight custom-made maps of Emerson's haunts and wide-ranging lecture itineraries, as well as a new four-part chronology of his life placed alongside both national and international events as well as major inventions. Mr. Emerson's Revolution provides essenti al reading for students and teachers of American intellectual history, aboliti on and the women's rights movement-and for anyone interested in the nineteenth-century roots of these seismic social changes.